Is the Chinese construction industry moving towards a knowledge- and technology-intensive industry?. (20th June 2020) - Wang, Yuhe; Ye, Gui; Zhang, Yuxin; Mu, Ping; Wang, Hongxia
Abstract: Total factor productivity (TFP) is a sustainable driver of economic growth, and TFP-driven growth is of great importance for a knowledge- and technology-intensive industry. However, there is a massive gap between theoretical research and practical observations on the role that TFP has played in driving construction growth since the global financial crisis. The understanding of this TFP role may shake and even change the traditional notion that the Chinese construction industry is a typical labor-intensive industry. To fulfill this gap, this paper presents an analysis on the driving effects of growth drivers in the industry. From the perspective of neoclassical growth theory, the Solow residual approach is applied to perform this analysis, where the growth drivers are decomposed into TFP, labor and capital. The data are collected from the China Statistical Yearbook on Construction and China Statistical Yearbook for the period of 2008–2016. Interestingly, the results indicate that during the surveyed period, the average driving effects of TFP, labor and capital were 45.08%, 39.95% and 14.97%, respectively. TFP was the first and foremost growth driver, but its driving effect has been facing a rigorous challenge from labor-driven effect. From an evolutionary perspective, the growth mostly driven by TFP occurred over 4 years (2008/09, 2011/12, 2012/13 and 2013/14), which accounted for 50% of the whole study period; the growth mainly driven by labor occurred in only 3 years (2009/10, 2014/15 and 2015/16). Given this situation, the Chinese construction industry can no longer be considered a labor-intensive industry; instead, it is believed to be moving from a labor-intensive industry to a knowledge- and technology-intensive industry. Highlights: TFP-driven growth is of great importance for a knowledge- and technology-intensive industry. The Chinese construction industry has long been regarded as a typical labor-intensive industry. The average driving effect of TFP during the period 2008-2016 was much larger than that of labor. The Chinese construction industry is thus considered to be moving towards a knowledge- and technology-intensive industry.